Survey of nurses’ knowledge and attitude regarding post operative pain management at a Teaching Hospital in Malaysia - Ho SE; Choy YC; Rozainiee A (Penerbit UKM, 2009)
Post operative pain is an expected adverse outcome following surgery and it often delays mobilization and overall recovery. Acute post operative pain is subjective and cannot be measured directly. The objective of this study was to determine nurses’ knowledge and attitude towards post operative pain management. A cross sectional study was conducted in surgical wards and the Intensive Care Unit of Universiti Kebangsaan Malaysia Medical Centre from February to April 2008. A 28 item questionnaire which comprised of two domains: knowledge and attitude towards post operative pain management was used. Eighty four respondents successfully responded to the study. Twenty respondents (25%) possessed high level, 58 respondents (69%) possessed moderate level and 5 respondents (6%) had low knowledge level of post operative pain management. Positive attitude towards post operative pain management was reported by 66 respondents (78.5%). There was a significant relationship between nurses’ academic qualifications and attitude towards post operative pain management (χ² =29.96, p <0.05). In conclusion, nurses in UKMMC possessed moderate level of knowledge and positive attitude towards post operative management. Results of this study show the need to enforce continuing medical education in pain management amongst UKMMC nurses in enhancing the quality of post operative care.